Industrial biotechnologies: Global technology trends - Molochaeva Luiza; Suleymanov Magomed; Mutsalova Satsita (E3S Web of Conferences, 2023)
Because of the depletion and deterioration of fossil sources of raw materials, adverse climate change in populations, pollution, environmental pollution and other factors, it is important to develop a bioeconomy based on its use of new resources of raw materials and technology for processing them. It is worth noting that the most important task for development of industrial biotechnology, the pharmaceutical industry and forest complex, bioenergy and other products has to provide new raw materials with the required properties. In many ways, the problem is resolved by creating fast-growing plant for different purposes obtained by biotechnological methods, and also to obtain non-traditional renewable raw materials (microalgae, biomass of cultivated cells from high plants, etc.). Another special place is occupied by technologies for the production and use of unicellular organisms (microalgae, yeast and bacterial producers), as well as technologies for the production and use of unicellular organisms (microalgae, yeast and bacterial producers), as well as plant transformants. Plant transformants and microclonal propagation are also used in this field.